IMPLEMENTATION SERVICE OF APPLICATION INOVATION SAMBANG PEMOHON IN IMMIGRATION OFFICE CLASS II NON TPI BLITAR ON PUBLIC SERVICES - Hardi Mustika Aji (Polteknik Imigrasi, 2019)
The application of information technology and an innovation found in immigration, especially at the Immigration Office, is a very important thing to always pay attention to and develop its development in the very long term, one of which is the focus on changes in terms of services at the office. With the existence of research in offices that has created an innovation regarding service and can produce several comparisons between before the innovation was made, and after the innovation was made. The results of the study conducted with this qualitative research method have explained that the immigration information technology system and an innovation in the Immigration Office still has an analysis and evaluation of making innovations that have an impact on services, and can be a development of the innovation application system. So, it is necessary to make several further studies or research related to the development of innovation in immigration information technology systems both at the Immigration Office and at other agencies that have an innovation related to the use of applications for services.